Terá a teleconsulta impacto na morbimortalidade dos doentes com patologias crónicas? - Gonçalo Domingos, Inês (2022)
Objectives: To establish if there are differences between the use of teleconsultation and the usual care in patients with one or more chronic diseases, followed in primary or secondary healthcare, in association with the reduction of morbidity and mortality.  Data sources: MEDLINE/PubMed, NHS Evidence, The Cochrane Library e Turning Research Into Practice. Methods: Search of observational studies, clinical trials, systematic reviews, and meta-analyses in Portuguese and English, published between January 2000 and August 2020 with the MeSH terms ‘Chronic Disease’, ‘Telemedicine’, ‘Remote Consultation’, ‘Primary Health Care’ and ‘General Practice’. To assess the evidence levels and recommendation importance it was used the Strength of Recommendation Taxonomy (SORT) scale of the American Family Physician. Results: Two hundred and sixty articles were obtained, of which only eight met the inclusion criteria. Five of the studies showed significant benefits in morbidity and mortality criteria, with the use of teleconsultation versus the use of usual care, such as: improvement in quality of life and a decrease in the number of hospitalizations of patients with multiple comorbidities; minimization of aching symptoms and depression, associated with chronic musculoskeletal pain; decreasing of hospitalization and mortality from all causes and reduction of the use of additional health care support in case of heart failure. Two studies showed the results between patients with access to teleconsultation and patients with usual care, in relation to the number of exacerbations, the use of additional health care assistance in asthmatic patients; number and duration of re-hospitalization in patients with chronic obstructive pulmonary disease or heart failure and concerning mortality and use of additional health care support by patients with multiple comorbidities. Conclusion: This revision showed that there is no obvious consensus regarding the results of morbidity and mortality indication criteria, in patients with chronic diseases, supported by teleconsultation. Nevertheless, the majority of the studies manifested the benefit of the use of teleconsultation in such criteria, compared to the patients supported by the usual consultation methods. Although not concordant, regarded studies demonstrated results at least overlapping, and not inferior, in the use of telemedicine when compared to the usual follow-up of patients. Even so, regarding the quality of the considered studies, there are needed more studies in this area to increase the viability of the results demonstrated, and allow the consequent generalization to the daily and normalized clinical practice.